Capital and sustainability on performance: The Mediating Effect of Governance - Laurens, Sebastianus; Murwaningsari, Etty (Technium Social Sciences Journal, 2021)
This article is to analyze the impact of intellectual capital and triple bottom line toward the dependent variable, using governance as moderating variable in order to strengthen the impact or otherwise. Current research regarding to this topic has grown broadly. Nevertheless, just a few researchers imply the whole component of the Good Corporate Governance as their moderating variable. This research utilizes the entire component (TARIF) in conjunction with the intellectual capital index, three bottom line indexes with ROA and number of awards, all these disclosures are essentials for this research. Gathering all the companies who publishes their sustainability report on their company website showed that there are limited resources to analyze. The results of this research demonstrated that triple bottom line does not impact both dependent variables; meanwhile intellectual capital has an impact to the non-financial performance. Governance showed that this variable has no role as a moderating variable to the effect of both dependent variables. The implication of this research is the companies should focus on intellectual capital to promote company’s performance and longevity.